Upper Eocene travertine‐lacustrine carbonate in the Jianchuan basin, southeastern Tibetan Plateau: Reappraisal of its origin and implication for the monsoon climate. (5th July 2021) - Sakuma, Aki; Kano, Akihiro; Kakizaki, Yoshihiro; Tada, Ryuji; Zheng, Honbo
Abstract: The Asian monsoon is one of the largest climatic systems in the world, but age of its onset has been estimated differently ranging from the late Eocene to the Quaternary. We investigated the sedimentology and stable isotopic compositions of the upper Eocene Jiuziyan Formation, a terrestrial limestone unit in the Jianchuan basin, Yunnan Province in China. This limestone formation is restricted in several localities in the central part of the basin. Previously, this has been characterized as palustrine carbonate and the transition to the sublacustrine deposit of the overlying Shuanghe Formation was interpreted as the appearance of wetter climate during the late Eocene. Our observations of macro‐ and microfacies revealed sedimentary fabrics indicating rapid CaCO3 precipitation, such as dendritic calcite and calcified reed stems, which are unlikely to develop in a simple lacustrine setting. High carbonate content (mostly >90 %) and restricted distribution of the Jiuziyan limestone indicate a depositional setting spatially limited and isolated from clastic influx. These findings, together with clearly higher δ 13 C values (−0.7 ‰ to +6.9 ‰) and lower δ 18 O values (−14.6 ‰ to −10.5 ‰) than those of the Shuanghe Formation, indicate that the limestone was mainly travertine, carbonate formed from endogenic spring water. The elevated δ 13 C resulted from a large amount of CO2 degassing from spring water with high p CO2 . In addition, the occurrence of centimeter‐scale lamination coupled with cyclic changes in δ 13 C and δ 18 O is almost identical with the modern annually‐laminated travertine reported from Baishuitai in northern Yunnan Province, implying comparable amplitude of seasonal temperature and precipitation changes to the record of the modern travertine at Baishuitai. Our results do not contradict the previous interpretation of late Eocene wetting and additionally suggest the existence of the late Eocene monsoon climate in the Jianchuan basin.